Research on the Protection and Inheritance Strategies of Intangible Cultural Heritage: The Case of Traditional Tujia Brocade Weaving Technique in China - Wang Peng ,; Ruangchewin , Puvasa; Panthupakorn, Poradee (Journal of Roi Kaensarn Academi, 2024)
Research purpose: This paper analyzes the inheritance dilemma faced by the traditional brocade weaving skills of the Tujia ethnic group in order to explore the specific implementation measures and effective mechanisms for inheritance protection. Research Methods: The author of this paper organizes relevant data and literature, and with the help of cultural management theory, locates and constructs strategies for the protection and inheritance of intangible cultural heritage in Longshan County of Hunan Province and Laifeng County of Hubei Province, and analyzes the protection and inheritance of traditional brocade weaving skills of the Tujia ethnic group in the following four aspects: originality, wholeness, sustainability, and decidability, by applying the idea of inheritance protection. Research Findings: The protection and inheritance of traditional and ethnic cultures are undergoing great challenges, and a large number of excellent intangible cultural heritages, including Tujia brocade, have been subjected to unprecedented impacts in this process. Research application: The conclusions of this study show that specific implementation measures and effective mechanisms for transmission protection are conducive to promoting the protection and transmission of intangible cultural heritage. This paper provides some experiences and ideas for the protection and transmission of the traditional brocade weaving skills of the Tujia ethnic group and discusses the direction and development trend of future research.